(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to exploration of informative potential of the historical sources covering spiritual and everyday life of North Trans-Azov territories (Priazovye) population in 20-30-ies of the XXth century by the example of Yeliseevka village (Primorsky district of Zaporizhzhya region). The following conclusion is grounded, that beliefs, spiritual and everyday life of the villagers had almost no differences from general traditional scheme.